2019
DOI: 10.1002/ppul.24584
|View full text |Cite|
|
Sign up to set email alerts
|

Urinary club cell protein 16 (CC16): Utility of its assay during acute bronchiolitis

Abstract: Acute bronchiolitis is responsible for high morbidity in infants. Club cell protein 16 kDa (CC16) is a major pneumoprotein secreted by club cells of the bronchial epithelium and eliminated by the renal pathway. CC16 seems to be a biomarker of epithelial damage in asthma. However, its value as a marker of acute bronchiolitis severity and later recurrent wheezing are uncertain, especially the value of its urinary assay for this purpose. A prospective, observational, analytical study was conducted at Clermont‐Fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Viral infections have an impact on SCGB1A1 levels: urine levels of SCGB1A1 are elevated in infants with acute bronchiolitis 41 and also children infected with respiratory syncytial virus (RSV) show elevated serum levels of the protein 42 . The susceptibility for viral infections may depend on the patient's serum SCGB1A1 levels: a study including elite athletes associated lower serum SCGB1A1 levels with a higher susceptibility to viral infections 43 .…”
Section: Secretoglobins In Diseases Of the Upper And Lower Airwaysmentioning
confidence: 99%
“…Viral infections have an impact on SCGB1A1 levels: urine levels of SCGB1A1 are elevated in infants with acute bronchiolitis 41 and also children infected with respiratory syncytial virus (RSV) show elevated serum levels of the protein 42 . The susceptibility for viral infections may depend on the patient's serum SCGB1A1 levels: a study including elite athletes associated lower serum SCGB1A1 levels with a higher susceptibility to viral infections 43 .…”
Section: Secretoglobins In Diseases Of the Upper And Lower Airwaysmentioning
confidence: 99%
“…However, serum CC16 levels were found to be similar in children infected with influenza or parainfluenza virus compared with healthy controls [ 62 ]. Recently, Egron et al measured both serum and urinary CC16 from the infants aged under 1 year hospitalized for acute bronchiolitis and found a urinary increase in CC16 correlating to the severity of acute bronchiolitis, suggesting the potential utility of urinary CC16 as a biomarker in acute bronchiolitis [ 63 ]. In adults, it has been reported that athletes who suffer from recurrent respiratory infections had significantly lower serum CC16 than controls, which might lead to the increased susceptibility to respiratory infections in athletes [ 64 ].…”
Section: Cc16 In Respiratory Infectionsmentioning
confidence: 99%
“…That is because nasal and sputum were not considered for CC16 measurements in most studies and when considered, the results were not comparable. Interestingly, CC16 from urine could be an accurate assessment for lung abnormality in children, such as asthma [ 73 ] and acute bronchiolitis [ 63 ]. Thus, we strongly recommend measuring CC16 from serum in adults and urine in children.…”
Section: Summary Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Club cell protein 16 (CC16) is the most abundant protein in the bronchoalveolar lavage fluid ( 29 , 30 ). It is encoded by the secretoglobin family 1A member 1 gene and serves an anti-inflammatory and antioxidant role in vivo ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%